Therapeutic potential of taurine in a pigmented rat model of age-related macular degeneration - Attia, Mohammed; Pavlovic, Tonja; Muliawan, Ashley; Tuya, Farjana; Mihalatos, Maria; Iwanicki, Marcin; Kang-Mieler, Jennifer (Frontiers in Ophthalmology, 2025)
PurposeTo investigate the potential protective effects of taurine supplementation against retinal degeneration in an animal model of mild dry age-related macular degeneration (AMD).MethodsTo test the effects of a taurine supplement in mild dry AMD, sodium iodate (NaIO3)-induced retinal degeneration model was used. Two administration methods, intraperitoneal (IP) and intravenous (IV), were used to deliver NaIO3 in pigmented Long Evans rats to generate mild and severe dry AMD, respectively. Structural abnormalities were evaluated in vivo using near-infrared (IR) reflectance fundus imaging and optical coherence tomography (OCT). Using the slow progressive mild AMD model, we investigated the neuroprotective effects of oral taurine supplementation (1.5% w/v in drinking water) against NaIO3-induced retinal degeneration over 20 weeks. In addition, a human Retinal Pigment Epithelium (RPE, hTERT-RPE1) cell culture model was used to directly assess taurine’s ability to protect against NaIO3-related oxidative stress.ResultsThe high-dose IV model (80 mg/kg) exhibited extensive and severe retinal damage, with ONL thinning by 64.2% and total retinal thickness (TRT) by 47.6%, predominantly in the peripapillary region. In contrast, the lower-dose IP model (50 mg/kg) displayed milder, more gradual deterioration (outer nuclear layer (ONL) thinning by 19.4% and TRT by 11.5%). Oral taurine supplementation significantly preserved ONL and TRT in vivo and supported RPE-1 cell survival, proliferation, and motility, under NaIO3 conditions.ConclusionTaurine supplementation provided significant structural protection against NaIO3-induced damage both in vivo and in cell culture, demonstrating its potential as a therapeutic candidate for mitigating mild dry AMD progression.